Associations between self-reported masticatory dysfunction and frailty: A systematic review and meta-analysis. - Gotaro Kojima; Yu Taniguchi; Masanori Iwasaki; Reijiro Aoyama; Tomohiko Urano (PLoS ONE, 2022)
Background Oral health is a key factor of overall health and closely associated with well-being and quality of life. Mastication is one the most important oral functions and may deteriorate with aging. Evidence on association between masticatory dysfunction and frailty in the literature is scarce and not coherent. Methods A search strategy was developed to conduct a systematic review of the literature in PubMed, CINAHL, and AMED in accordance with the PRISMA 2020 guidelines. We searched for studies published in 2000 or later that examined associations between self-reported masticatory dysfunction and frailty risk. The reference lists of the relevant articles were reviewed for additional studies. We calculated pooled odds ratios (OR) of association between self-reported masticatory dysfunction and the risk of frailty by fixed-effects meta-analysis. The Joanna Briggs Institute Critical Appraisal Checklist was used to assess risk of bias. Publication bias was assessed by visually inspecting a funnel plot. Results A total of 285 studies were identified by the literature search. Among 5 studies selected for this review, 4 cross-sectional studies including a total of 7425 individuals were used for meta-analysis. The pooled results by a fixed-effects model showed that there was a significant association between self-reported masticatory dysfunction and frailty risk (pooled OR = 1.83, 95%CI = 1.55-2.18, p<0.00001). There was no evidence of publication bias observed. Conclusions This systematic review and meta-analysis highlighted pooled cross-sectional evidence that community-dwelling older people who report masticatory dysfunction are significantly more likely to be frail than those who do not. The limitations of this study are: inclusion of only cross-sectional studies, no gold standard to measure masticatory functions, self-reported information on masticatory function, and the limited number of included studies. More longitudinal studies are warranted for further understanding of the causal pathways and elucidate underlying mechanisms. Registration: PROSPERO CRD42021277173.